2008
DOI: 10.1159/000113516
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-Beta-Hexosaminidase Activity in Asthma

Abstract: Background: N-acetyl-β-hexosaminidase (β-hex) is a lysosomal hydrolase, which is selectively secreted into the extracellular space by inflammatory cells. The aim of our study was to assess the activity of β-hex in the plasma of asthmatic patients, and to establish whether it correlates with asthma severity and airway inflammation. Methods: The study was conducted in a group of 46 asthmatic patients and 13 healthy volunteers. All study participants underwent analysis of exhaled nitric oxide and flow-volume spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Glycoprotein endogenous ligands for MR ( β -Hex A and B, aka NAGA (N-Acetyl- β , D-Glucosaminidase), NAG, and NAGase) are elevated in bronchoalveolar lavage fluids of guinea pigs exposed to ozone [4] and in serum of asthmatic patients, more so in severe asthmatics [27]. Moreover, gene variants of glycoprotein and resulting abnormal serum levels of the respective glycoproteins are associated with asthma [28].…”
Section: Discussionmentioning
confidence: 99%
“…Glycoprotein endogenous ligands for MR ( β -Hex A and B, aka NAGA (N-Acetyl- β , D-Glucosaminidase), NAG, and NAGase) are elevated in bronchoalveolar lavage fluids of guinea pigs exposed to ozone [4] and in serum of asthmatic patients, more so in severe asthmatics [27]. Moreover, gene variants of glycoprotein and resulting abnormal serum levels of the respective glycoproteins are associated with asthma [28].…”
Section: Discussionmentioning
confidence: 99%
“…Bierc et al [ 12 ] noted a significant increase in HEX, GLU, and GAL activity in the salivary gland tumor tissue, while Waszkiewicz et al [ 13 ] reported that HEX determination may be a useful marker for salivary dysfunction caused by a single dose of ethanol. Determination of lysosomal exoglycosidases also appears to have a significant diagnostic value in screening and monitoring chronic periodontitis [ 14 ], cancer [ 12 , 15 ], asthma [ 16 ], alcohol dependence [ 17 , 18 ], Lyme borreliosis [ 19 ], and rheumatoid arthritis [ 19 , 20 ], as well as type 1 and type 2 diabetes mellitus [ 21 – 23 ]. It has been demonstrated that increased activity of lysosomal hydrolases in saliva reflects their elevated synthesis/release, which may be associated with lysosomal membrane damage [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, gene variants of glycoproteins, affecting serum levels of respective glycoproteins, have been reported as important factors in asthma [ 32 ]. Regarding glycoprotein endogenous ligands for MR, β -hexosaminidase levels are significantly elevated in serum of severe asthmatic patients [ 33 ]. There is also a growing interest in immunoregulatory capacity of glycans and glycan-binding proteins such as galactins, selectins (C-type lectins, MR is a ligand for L-selectin) [ 34 ], and siglecs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%